Experience of hypoglycaemia and strategies used for its management by community-dwelling adults with diabetes mellitus: a systematic review - Tan, P.; Chen, H.; Taylor, B.; Hegney, Desley (Blackwell Publishing, 2012)
Aim: To synthesise the evidence on how community-dwelling adults with type 1 and type 2 diabetes mellitus experience hypoglycaemia and the strategies they use to control it. Methods: Using a three-step search strategy, all published and unpublished qualitative studies in English from January 2000 to August 2010 were retrieved. Participants diagnosed with type 1 or type 2 diabetes mellitus, experienced in self-managing their hypoglycaemia, and who lived independently in the community and attended primary care or outpatient clinics were included. An initial limited search was conducted in MEDLINE and CINAHL to identify keywords and index terms, which were then used in a second search across the CINAHL, PUBMED, SCOPUS, PsycINFO, PsycARTICLES, Web of Science, JSTOR, EMBASE and MEDNAR databases. Additionally, the reference lists of all retrieved papers were hand-searched for additional studies. Retrieved studies were assessed for methodological validity using the standardised Joanna Briggs Institute-Qualitative Assessment and Review Instrument (JBI-QARI). Data, in terms of research findings, were extracted from included studies using the standardised JBI-QARI data extraction tool. Five studies (six papers) were included in the review. Results: The 20 findings from the six papers were grouped into three categories, which were then synthesised into one overall finding – that is ‘People with diabetes mellitus can self-manage their diabetes and thus prevent hypoglycaemic episodes more effectively when health professionals provide psychological, physiological and spiritual support, and an individually targeted education programme’.Conclusions: Within the constraints of this review, it appears that the patient-identified priority is to maintain normality in blood glucose self-management. There is also evidence that some people lack the knowledge to identify and self-manage hypoglycaemia. Implications for practice: To enable community-dwelling adults with diabetes mellitus to self-manage hypoglycaemia, healthcare professionals should provide individualised information and emotional support and regularly discuss and assess the person’s level of knowledge, awareness of hypoglycaemia and their ability to self-manage.